Phytogenic Feed Additive Influences on the Growth Performances, Serum Lipid Profile, Liver Functions and Antibacterial Activity of Broiler Chicks - Abedin, M.T.; Sujon, M.N.; Islam, M.N.; Sadiq, S.R.; Sayed , M.A. (International Journal of Poultry Science, 2021)
Objective: This investigation was performed to explore the combined effect of buckwheat (BW), black cumin (BC) and honeyweed (HW) supplemented diet on growth performances, blood metabolites and intestinal microflora of broiler chicks for the production of safe meat. Materials and Methods: A total of 60 day-old chicks (Cobb-500) were divided into four groups viz. T1(Commercial control, CC), T2 (Formulated Feed, FF+10% BW), T3 (FF+10% BW+1.5% BC+5% (w/v) HW powder), T4 (FF+10% BW+3% BC+5% (w/v) HW powder) in complete randomized design with three (3) replications, each of which contain 5 birds. Results: At the end of the 30 days, T3 diet significantly (p